The Collapse of Muslim Bourgeois in Java - Suharso Suharso (Diponegoro University, 2020)
This study was inspired by Clifford Geertz's success in reviving discussions about the role and presence of middle class Muslim bourgeois traders in Java, especially in Kudus. The indigenous bourgeois had existed before Indonesian independence. This class was expected to be the core of the middle class to carry out social, economic, and cultural developments and reforms. Bourgeois representation indigenous traders in the western area, known as Kudus kulon. Its community was expected to be an agent of change and a source of entrepreneurship for the modern community. However, this prediction was not proven. Especially after Indonesia's independence, the role of the middle-class bourgeois of Javanese Muslim traders was getting declined. Therefore, this study conducted using a historical approach through archival studies and interviews to prove the truth of these predictions. Based on the results of field study, it is known that the Islamic student class living in Kudus kulon were considered as the most potential and had certain values to develop themselves into a strong and independent entrepreneurs class. However, the strength of the Muslim traders’ network diminished due to unfavorable economic conditions for the traditional business of santri (Islamic students) during the New Order.